Faktor Belia Tidak Bekerja Dari Perspektif NEET - Rusmawati Said; Zulkarnain Yusop; Azmawani Abdul Rahman; Yuhanis Abd Aziz; Mohd Rizal Mohd Sham; Asmaddy Haris (Institut Penyelidikan Pembangunan Belia Malaysia, 2024)
Jilid :14